On war - Heuser, Beatrice; Clausewitz, Carl von, 1780-1831. (Oxford : Oxford University Press, 2007)
This analysis of the phenomenon of war by Clausewitz, a Prussian officer who fought against the French during the Napoleonic Wars, presents the human, social, tactical, and technological factors that affect a war's outcomes and discusses how political purpose, chance, and enmity combine to shape a war's dynamics.
Abridged with an introduction and notes by Beatrice Heuser.
Includes bibliographical references and index.
Translated from the German.
Keywords: War; Military art and science; Armed Conflicts; Military Science; Military art and science; War